Chronic Mitral Regurgitation: When the Optimal Timing of Surgical Intervention? - Oemar, H; Yusoff, K; Abdulgani, HB (Cardiovascular Journal, 2011)
Optimal timing of surgery in mitral regurgitation (MR) is a complex problem that has been studied widely. The pathophysiological mechanism and hemodynamic changes whereby MR exerts its deleterious effects on survival is well recognized. Early reports in the literatures and newer prospective studies suggest that severe MR is not a benign state and it has a high morbidity and eventually mortality. Thus, it is obviously rationale in understanding pathophysiological construct and be able to identify disease condition in choosing the golden moment for surgical intervention. Surgical intervention has been exposed to be the only efficient management, but its optimal timing remains a matter of controversy. The ultimate goal of patient care is obviously no longer the relief of limiting symptoms but the achievement of an optimal long-term outcome with regard to mortality and morbidity. Preoperative developments of severe symptoms, left ventricular (LV) dysfunction, LV enlargement, chronic atrial fibrillation, or progressive pulmonary hypertension were found to be associated with an unfavorable outcome. The timing of surgical correction for MR depends chiefly on three factors: clinical symptoms, LV function and the severity of MR. In term of waiting symptoms, the surgery has changed considerably from a relatively passive response to the development of severe symptoms, to an early surgery concept preceding the signs of LV dysfunction. This because clinical symptoms can remain absent or minimal despite severe regurgitation caused by adaptive remodeling of LV and left atrium, or because of patient adaptation of the disease. Thus, in chronic severe MR, there should be no waiting for LV function to decline before intervening, because the long-term results of that approach are not gratifying. Recent data underscored that mitral surgery is associated with a considerably decreased subsequent risk of mortality and heart failure. The reduction in the risk of death associated with surgery is greater among patients with a larger effective regurgitant orifice (ERO) assessed echocardiographically than among those with a smaller ERO and results in normalization of the life expectancy. These data provide a firm basis for considering surgery in patients with asymptomatic chronic mitral regurgitation who have an ERO of at least 40 mm². Key words: Mitral regurgitation; Mitral valve surgery; Echocardiography. DOI: http://dx.doi.org/10.3329/cardio.v1i2.8120 Cardiovasc. j. 2009; 1(2) : 142-147